2007
DOI: 10.1523/jneurosci.1064-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Heterogeneity of Calcium Signaling at Single Presynaptic Boutons of Cerebellar Granule Cells

Abstract: res transients while loading boutons to a steady-state indicator concentration. These experiments revealed that, in the absence of exogenous calcium buffers, a single action potential evokes transients of Ca res that vary widely in different boutons both in amplitude (400 -900 nM) and time course (25-55 ms). Variation in calcium influx density, endogenous buffer capacity, and calcium extrusion density contribute to differences in Ca res among boutons. Heterogeneity in Ca res within different boutons suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
107
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 55 publications
(66 reference statements)
13
107
2
Order By: Relevance
“…This approach suggested that at the calyx of Held vesicle fusion is triggered by a calcium increase of 25 μM lasting several hundred microseconds (Schneggenburger and Neher, 2000). Ca res is readily measured with fluorometric calcium indicators, and it is typically tens to a few hundred nanomolar (Atluri and Regehr, 1996; Brenowitz and Regehr, 2007; Scott and Rusakov, 2006). …”
Section: Proposed Mechanisms Of Facilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach suggested that at the calyx of Held vesicle fusion is triggered by a calcium increase of 25 μM lasting several hundred microseconds (Schneggenburger and Neher, 2000). Ca res is readily measured with fluorometric calcium indicators, and it is typically tens to a few hundred nanomolar (Atluri and Regehr, 1996; Brenowitz and Regehr, 2007; Scott and Rusakov, 2006). …”
Section: Proposed Mechanisms Of Facilitationmentioning
confidence: 99%
“…During the action potential, local Ca 2+ rises to 25 μM briefly (FWHM = .34 ms, Sabatini and Regehr, 1998)). After the action potential, a residual Ca 2+ signal of 400 nM decays back to resting Ca 2+ (50 nM) with a 40 ms time constant (Brenowitz and Regehr, 2007). …”
Section: Figurementioning
confidence: 99%
“…An alteration in the firing threshold for somatic or extracellular activation that involves the Na/K-ATPase could contribute to short-term depression at these synapses (Munoz-Cuevas et al 2004). A failure of an action potential to invade some axonal branches may contribute to depression in cultured hippocampal cells (Brody and Yue 2000;Prakriya and Mennerick 2000), but action potential invasion of axons is generally reliable in more intact tissue (Cox et al 2000;Kreitzer and Regehr 2001;Brenowitz and Regehr 2007).…”
Section: Inactivation Of Calcium Channels and Other Mechanisms Of Depmentioning
confidence: 99%
“…In cerebellar granule cells, Brenowitz and Regehr (2007) found low variability of AP-stimulated calcium influx in boutons due to a large number of calcium channels. At giant mossy fiber boutons in hippocampal area CA3 studies of calcium transients following action potential stimulation determined that store-released calcium contributes roughly one-fifth of the Ca 2+ signal (Scott and Rusakov, 2006).…”
Section: Imaging Calcium Transientsmentioning
confidence: 92%